(untitled) (Journal of Nepalese Business Studies, 2016)
This paper examines the organizational commitment of female employees of Nepalese Financial Institutions (NFIs) and analyzes the factors affecting the organizational commitment. A structured questionnaire has been distributed to the female employees of NFIs. Financial Institutions have been stratified into three strata namely commercial bank, development bank and finance companies situated at Lekhnath municipality and Pokhara sub-metropolitan city. Stratified random sampling method has been applied for sampling. The sample size for this study is 122. The paper employs 18 statement questionnaire developed by Mowday, Steers, and Porter as measure of organizational commitment (OC) which is used as the dependent variable in the study. Additionally, communication, career development and role of employee, working condition, recognition and reward, role of immediate supervisor and training program as factors of job satisfaction have been considered as independent variables. Descriptive analysis has been used to find frequency, mean, and percentage. Statistical tools like correlation, independent sample t test, ANOVA, and multiple regression analysis have been employed. The study reveals that the female employees in NFI are found to have moderate level of organizational commitment. No significant difference is found in the OC level of the employees by marital status, job position, organizational status, educational level, and service year except the age of employee. The organizational commitment of the employees is found to be effected significantly by role of supervisor and training programme of organization. Moreover, for married employees role of supervisor is found to be important factor for organizational commitment while for single employees training programme is found to be more important. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp.126-136